2015
DOI: 10.1186/s12883-015-0298-0
|View full text |Cite
|
Sign up to set email alerts
|

APOE ε4 moderates abnormal CSF-abeta-42 levels, while neurocognitive impairment is associated with abnormal CSF tau levels in HIV+ individuals – a cross-sectional observational study

Abstract: BackgroundCerebrospinal fluid (CSF) biomarkers Aβ1-42, t-tau and p-tau have a characteristic pattern in Alzheimer’s Disease (AD). Their roles in HIV-associated neurocognitive disorder (HAND) remains unclear.MethodsAdults with chronic treated HIV disease were recruited (n = 43, aged 56.7 ± 7.9; 32% aged 60+; median HIV duration 20 years, >95% plasma and CSF HIV RNA <50 cp/mL, on cART for a median 24 months). All underwent standard neuropsychological testing (61% had HAND), APOE genotyping (30.9% carried APOE ε4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 43 publications
5
31
0
Order By: Relevance
“…Our results show that CSF IFNα levels negatively correlate with multiple measures of neurocognitive function, including a composite score that reflects global performance. These correlations may have been driven by participants with more significant impairment (a GDS of ≥1.5 as suggested by other studies) (Cysique et al , 2015). Participants with GDS ≥1.5 had significantly higher CSF IFNα levels.…”
Section: Discussionmentioning
confidence: 67%
“…Our results show that CSF IFNα levels negatively correlate with multiple measures of neurocognitive function, including a composite score that reflects global performance. These correlations may have been driven by participants with more significant impairment (a GDS of ≥1.5 as suggested by other studies) (Cysique et al , 2015). Participants with GDS ≥1.5 had significantly higher CSF IFNα levels.…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, endolysosomes have been implicated in the pathogenesis of sporadic AD (Tate and Mathews, 2006; Boland et al, 2008) and HAND (Gelman et al, 2005; Spector and Zhou, 2008; Zhou and Spector, 2008; Cysique et al, 2015). Neurons, as long-lived post-mitotic cells, are especially vulnerable to perturbations of endolysosome pH and by maintaining an acidic environment endolysosomes are able to control the integrity of quality of critical proteins (Nixon and Cataldo, 1995; Bonaldo and Sandri, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[42] In another study ApoE ε4 was found to moderate the expression of amyloid in HAND subjects, although the authors failed to find a direct association between ApoE ε4 carrier status and HAND. [43] Similarly, autopsy findings showed that the presence of diffuse amyloid plaques was associated with HAND among ApoE ε4 carriers, but not in non-ε4 carriers, suggesting that ApoE isoforms differently moderate the association between amyloid aggregation and HAND. [44]…”
Section: Neuropathology Of Hiv In the Current Era And Overlap With Admentioning
confidence: 99%